(untitled) (Intent Research Scientific Journal, 2025)
Space in literary texts serves as more than just a backdrop for narrative action; it is a dynamic element that shapes meaning, influences characters, and reflects thematic concerns. This article explores the multifaceted functions of space in literature, examining how physical, social, and psychological spaces contribute to storytelling. Through an analysis of selected literary works, the study highlights the ways in which space can symbolize power, evoke emotions, and structure narrative progression. The findings underscore the importance of space as a critical literary device that enriches readers’ engagement with texts.